In-depth Analysis of the Effects of Smart Services on Value Creation - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Buss, Eugen (Proceedings of the ISPIM Connects Bangkok – Partnering for an Innovative Community)

Value-centered design of a digital service robotics platform - Menzefricke, Jörn Steffen; Frank, Maximilian; Drewel, Marvin; Dumitrescu, Roman (Procedia CIRP)

Identification of socio-technical changes caused by Industry 4.0 - Schnasse, Felix; Menzefricke, Jörn Steffen; Gabriel, Stefan; Hobscheidt, Daniela; Parlings, Matthias; Kühn, Arno; Dumitrescu, Roman (Proceedings of the Hamburg International Conference of Logistics (HICL))

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Method for data inventory and classification - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Data-Driven Product Generation and Retrofit Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Wendt, Niklas; Dumitrescu, Roman (Procedia CIRP)

Datengetriebene Steigerung der Verfügbarkeit - Uhlmann, Eckart; Dumitrescu, Roman; Polte, Julian; Meyer, Maurice; Simsek, Deniz (wt Werkstattstechnik online)

Framework for Data Analytics in Data-Driven Product Planning - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia Manufacturing)

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

The impact of the 4th industrial revolution on the design fields of innovation management - Niewöhner, Nadine; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Der Industrie 4.0 Maturity Index in der betrieblichen Anwendung. Aktuelle Herausforderungen, Fallbeispiele und Entwicklungstrends (acatech KOOPERATION) - Schuh, Günther; Anderl, Reiner; Dumitrescu, Roman; Krüger, Antonio; ten Hompel, Michael

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; Enzberg, Sebastian von; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Procedia CIRP)

Gestaltung hybrider Wertschöpfung und Arbeit im Kontext von Smart Services - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman; Frank, Maximilian; Schweppe, Thomans; Melzer, Annegret (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Strategie als Erfolgsfaktor - Koldewey, Christian; Dumitrescu, Roman (ServiceToday)

Development Process for Smart Service Strategies - Koldewey, Christian; Evers, Hans Heinrich; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Proceedings of The XXX ISPIM INNOVATION CONFERENCE)

Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)

Servicerobotik kooperativ entwickeln - Kahl, Björn; Kogan, Yevgen; Menzefricke, Jörn Steffen (Computer & Automation)

Smart Service-Innovationen - Gewusst wie - Koldewey, Christian; Reinhold, Jannik; Willmes, Georg; Michels, Jan Stefan (markt & wirtschaft westfalen - Das Wirtschaftsmagazin für zukunftsorientierte Unternehmer)

Entwicklung von Smart Service Strategien - Koldewey, Christian; Gausemeier, Jürgen; Fischer, Stefan; Kage, Martin (Symposium für Vorausschau und Technologieplanung)

Strategische Planung des Wertschöpfungsbeitrags von HELLA für automatisiertes Fahren von morgen - Eckelt, Daniel; Bismark, Ronny; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Vorausschau und Technologieplanung)

Model Checking of Integratively Designed Product and Production Systems - Dumitrescu, Roman; Japs, Sergej; Kaiser, Lydia; Rasor, Rik (TdSE 2019)

Entwicklung einer Suchstrategie für ein medienbasiertes Technologiesanning am Beispiel der Antriebstechnik - Albers, Alexander; Ellermann, Kai Fabian; Kühn, Arno; Dumitrescu, Roman (15. Symposium für Vorausschau und Technologieplanung)

Einstieg in die Plattformökonomie - Drewel, Marvin; Gausemeier, Jürgen; Vaßholz, Mareen; Homburg, Nils (Symposium für Vorausschau und Technologieplanung)

Erfolg versprechende Industrie 4.0-Zielposition - Ermittlung unter Berücksichtigung zukünftiger Umfeldentwicklungen - Pierenkemper, Christoph; Reinhold, Jannik; Dumitrescu, Roman; Gausemeier, Jürgen (Industrie 4.0 Management)

Developing and Evaluating Concepts for a Digital Platform - Wortmann, Fabio; Joppen, Robert; Drewel, Marvin; Kühn, Arno; Dumitrescu, Roman (IAMOT 2019 – Proceedings of the 28th International Association for Management of Technology Conference, Apr. 2019 International Association for Management of Technology (IAMOT), IAMOT)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects)
Today's manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding value networks fundamentally differ from traditional ones. Developing smart services requires new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to adapt their value networks. However, the highly complex transformation of value crea-tion especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this paper, we introduce a basic framework for planning smart services and present a methodology for competence-based plan-ning of value networks for smart services in three phases: Smart service analysis, competence analysis and value creation planning. The methodology is explained by an example from tooling machine industry.

Reference Architecture and Classification of technology-induced Scenarios of Digitized Work - Bansmann, Michael; Foullois, Marc; Roeltgen, Daniel; Wöste, Lars; Dumitrescu, Roman (28th IAMOT International Conference of the International Association for Management of Technology, Mumbai, Indien)

Framework for the configuration of an engineering based Makeathon - Asmar, Laban; Wortmann, Fabio; Röltgen, Daniel; Niewöhner, Nadine; Kühn, Arno; Dumitrescu, Roman (Proceedings of ISPIM Innovation Conference, 7.-9. April, Ottawa, 2019)

An analysis of barriers for the introduction of Systems Engineering - Bretz, Lukas; Kaiser, Lydia; Dumitrescu, Roman (Procedia CIRP Volume 84)

Requirement Profiles as a Foundation for customer-centric Ideation in Business-to-Business Markets - Albers, Alexander; Tekaat, Julian; Kühn, Arno; Dumitrescu, Roman (29th CIRP Design 2019, Porto, Portugal, May 8th - May 10th, 2019)

Innovationen für die Märkte von morgen – Strategische Planung von Produkten, Dienstleistungen und Geschäftsmodellen - Gausemeier, Jürgen; Dumitrescu, Roman; Echterfeld, Julian; Pfänder, Tomas; Steffen, Daniel; Thielemann, Frank

Sociotechnical solution patterns for the development of smart products - Hobscheidt, Daniela; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman (29th CIRP Design 2019, Povoa de Varzim, Portugal, May 8th - May 10th, 2019)

Using existing industry 4.0 knowledge for the assessment of SME innovation-demands - Hobscheidt, Daniela; Fechtelpeter, Christian; Kühn, Arno; Dumitrescu, Roman (ISPIM Innovation Conference, Florence, Italien, 16.-19. Juni, 2019)

Key Performance Indicators in the Production of the Future - Joppen, Robert; von Enzberg, Sebastian; Gundlach, Jan; Kühn, Arno; Dumitrescu, Roman (52nd CIRP Manufacturing Systems Conference, Ljubljana, 2019)

Nationales Kompetenz-Monitoring - Bericht: Energiespeichersysteme (Fokus Lithium-Ionen-Speicher) - Gausemeier, Jürgen; Guggemos, Michael; Kreimeyer, Andreas; Lange, Thomas; Behrens, Jan Henning; Seitz, Ralph; Ortloff, Luise; Frey, Anna; Dachsberger, Stephanie; Drewel, Marvin; Frank, Maximilian

Prävention gegen Produktpiraterie - Innovationen schützen; Intelligente Technische Systeme - Lösungen aus dem Spitzencluster it's OWL - Plass, Christoph; Altemeier, Katharina; Frank, Maximilian; Jahnke, Ulrich; Steffen, Daniel

Investitionsbewertung vor dem Hintergrund der Digitalisierung am Beispiel Schaltschrankbau - Joppen, Robert; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb (ZWF))

Designing Business Models for Augmented Reality - Röltgen, Daniel; Wortmann, Fabio; Grote, Eva-Maria; Dumitrescu, Roman (Proceedings of the 28th International Conference of the International Association for Management of Technology, April 7-11, Mumbai, 2019)

An Explanatory Model as Basis for the Introduction of Systems Engineering and capable IT-Infrastructures in Industry - Heihoff-Schwede, Joerg; Bretz, Lukas; Kaiser, Lydia; Dumitrescu, Roman (IEEE ISSE 2019, Edinburgh, Scotland, 2019)

Potentials for the Integration of Design Thinking along Automotive Systems Engineering focusing Security and Safety - Tekaat, Julian; Kharatyan, Aschot; Anacker, Harald; Dumitrescu, Roman (Proceedings of the International Conference on Engineering Design (ICED 19), 5.-8. August 2019, Delft, Niederlande, 2019)

Typisierung und Strukturierung digitaler Plattformen im Kontext Business-to-Business - Wortmann, Fabio; Ellermann, Kai Fabian; Kühn, Arno; Dumitrescu, Roman (Vorausschau und Technologieplanung, 15. Symposium für Vorausschau und Technologieplanung, 21.-22. November 2019, Berlin)

Smart Services – Konzept einer neuen Marktleistung - Frank, Maximillian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)

Pattern based development of digital platforms - Drewel, Marvin; Gausemeier, Jürgen; Koldewey, Christian; Özcan, Leon (Proceedings of the 2018 ISPIM Connects)

Datenbrillen im Kontext Industrie 4.0 – Bewertung von Anwendungsszenarien von Augmented Reality auf Basis einer Technologie-Roadmap - Röltgen, Daniel; Bansmann, Michael; Nickchen, Daniel; Wortmann, Fabio; Dumitrescu, Roman (14. Symposium für Vorausschau und Technologieplanung)

Data Map - Method for the Specification of Data Flows - Joppen, Robert; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (CIRP ICME, Neapel, 18. - 20. Jul. 2018)

Method for Collecting Data in the Assesment of Investments - Joppen, Robert; Kühn, Arno; Dumitrescu, Roman; Hupach, Dominik (CIRP ICME, Neapel, 18. - 20. Jul. 2018)

Requirements Profiles as a Basis for Ideation in Product Generation Planning - Albers, Alexander; Tekaat, Julian; Kühn, Arno; Dumitrescu, Roman (R&D Management Conference 2018, 30. Jun. - 4. Jul. 2018)

Internet of Things Canvas for Ideation in Model-Based Product Generation Planning - Albers, Alexander; Bernijazov, Ruslan; Kaiser, Lydia; Dumitrescu, Roman (IEEE - 13th System of Systems Engineering Conference, 19. - 22. Jun. 2018)

Feature model for the specification of industrial indoor location-based services (I²LBS) - Falkowski, Tommy; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman (SysInt Conference, 19. - 20. Jun. 2018)

Demand-orientated and sociotechnical solution patterns for digital transformation in SMEs - Hobscheidt, Daniela; Lipsmeier, Andre; Dumitrescu, Roman (ISPIM Conference - The Name of the Game, 17. - 21. Jun. 2018)

Transfering Technology induced scenarios of digitized work - Bansmann, Michael; Fechtelpeter, Christian; Anacker, Harald; Dumitrescu, Roman (XXIX ISPIM Innovation Conference 2018, 17. - 20. Jun. 2018)

Planning of scalable Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen (Proceedings of the 2018 ISPIM Innovation Conference , Jun. 2018 International Society for Professional Innovation Management (ISPIM))

Building blocks for planning and implementation of smart services based on existing products - Mittag, Tobias; Rabe, Martin; Gradert, Till; Kühn, Arno; Dumitrescu, Roman (CIRP IPS², Linköping, 29. - 31. Mai 2018)

Analytics Canvas – A Framework for the Design and Specification of Data Analytics Projects - Kühn, Arno; Joppen, Robert; Reinhart, Felix; Röltgen, Daniel; von Enzberg, Sebastian; Dumitrescu, Roman (28th CIRP Design Conference 2018, Nantes, 23. - 25. Mai 2018)

Maturity Model-Based Planning of Cyber-Physical Systems in the Machinery and Plant Engineering Industry - Westermann, Thorsten; Dumitrescu, Roman (DESIGN Conference 2018, 21. - 24. Mai 2018)

Planning of Smart Services based on a Reference Architecture - Rabe, Martin; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (International Design Conference 2018, Dubrovnik, Kroatien , 21. - 24. Mai 2018)

Smart Services - Konzept einer neuen Marktleistung - Frank, Maximilian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Zukunftsorientierte Leistungssteigerung von Unternehmen durch Industrie 4.0 - Pierenkemper, Christoph; Drewel, Marvin; Gausemeier, Jürgen (Tagungsband AALE 2018 - Das Forum für Fachleute der Automatisierungstechnik aus Hochschulen und Wirtschaft, 15. Konferenz für Angewandte Automatisierungstechnik in Lehre und Entwicklung (AALE))

Morphological business model analysis to derive the dominant industry logic - Niewöhner, Nadine; Albers, Alexander; Rabe, Martin; Dumitrescu, Roman (Proceedings of the ISPIM Innovation Forum, Mrz. 2018 International Society for Professional Innovation Management (ISPIM))

A practical Framework for the Optimization of Production Management Processes - Joppen, Robert; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (The 16th Global Conference on Sustainable Manufacturing)

Supporting the planning phase of SME-tailored technology transfer projects - Fechtelpeter, Christian; Dumitrescu, Roman; Kühn, Arno (IAMOT 2018 - 27th International Association for Management of Technology Conference)

Entwicklung intelligenter technischer Systeme - Dumitrescu, Roman; Kühn, Arno; Thielemann, Frank; Steffen, Daniel (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Leistungssteigerung durch Industrie 4.0 für kleine und mittlere Unternehmen - Knospe, Olaf; Drewel, Marvin; Mittag, Tobias; Pierenkemper, Christoph; Hobscheidt, Daniela (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Toward A Design Approach For Industrial Indoor Location-Based Services (I²LBS) - Falkowski, Tommy; Günther, Matthias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman (DESIGN Conference 2018,)

Framework for the agile development of innovative Product-Service-Systems for existing physical rehabilitation systems - Asmar, Laban; Rabe, Martin; Low, Cheng Yee; Yee, Jingye; Kühn, Arno; Dumitrescu, Roman (4th International Conference on System-Integrated Intelligence: Intelligent, Flexible and Connected Systems in Products and Production)

Specification technique for augmented reality based product service systems - Röltgen, Daniel; Wortmann, Fabio; Dumitrescu, Roman (INTERNATIONAL DESIGN CONFERENCE - DESIGN 2018)

Eingesetzte wissenschaftliche Methoden - Kummert, Franz; Albers, Alexander; Bremer, Christian; Büttner, Sebastian; Dellnitz, Michael; Dumitrescu, Roman; Gräler, Manuel; Just, Viktor; Mucha, Henrik; Peitz, Sebastian; Röcker, Carsten; Trächtler, Ansgar; et al. (Ressourceneffiziente Selbstoptimierende Wäscherei – Ergebnisse des ReSerW-Projekts)

Systematic Development of Smart Factory using CONSENS - Mohammad, Ubaidullah; Low, Cheng Yee; Asmar, Laban; Rahman, Ramhuzaini Abd; Rabe, Martin; Dumitrescu, Roman; Zakaria, Noor Ayuni Che (4th International Conference on System-Integrated Intelligence: Intelligent, Flexible and Connected Systems in Products and Production)

PGE-Produktgenerationsentwicklung und Zukunftsvorausschau: Eine systematische Betrachtung zur Ermittlung der Zusammenhänge - Albers, Albert; Dumitrescu, Roman; Marthaler, Florian; Albers, Alexander; Kühfuss, Dennis; Strauch, Markus; Siebe, Andreas; Bursac, Nikola (14. Symposium für Vorausschau und Technologieplanung)

Identifikation von Potentialen für Augmented-Reality-basierte Produkt-Service-Systeme - Röltgen, Daniel; Wortmann, Fabio; Anacker, Harald; Dumitrescu, Roman (13. Symposium für Vorausschau und Technologieplanung, Band 374 , Berlin , 23. - 24. Nov. 2017)

Modellbasierte Entscheidungsunterstützung in der Produktgenerationenplanung - Albers, Alexander; Kühn, Arno; Dumitrescu, Roman (Proceedings of: Tag des Systems Engineering (TdSE), 8. - 10. Nov. 2017)

Mechatronic Modularization of Intelligent Technical Systems - Lipsmeier, Andre; Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman (21th International Conference on Engineering and Design (ICED17), 21. - 25. Aug. 2017)

Kundenorientierte Entwicklung von Intelligenten Technischen Systemen im Maschinenbau - Lipsmeier, Andre; Anacker, Harald; Dumitrescu, Roman; Kühn, Arno (Stuttgarter Symposium für Produktentwicklung SSP 2017, Stuttgart, 28. - 29. Jun. 2017)

Integrated technology transfer concept for fostering innovation in SMEs - Fechtelpeter, Christian; Kühn, Arno; Dumitrescu, Roman; Ebbesmeyer, Peter (Proceedings of the 26th International Association for Management of Technology Conference , 14. - 18. Mai 2017, IAMOT)

Erfolgsgarant digitale Plattform – Vorreiter Landwirtschaft - Drewel, Marvin; Gausemeier, Jürgen; Kluge, Andre; Pierenkemper, Christoph (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017, Band 369)

Implementation planning and transfer of technology induced scenarios of digitized work - Fechtelpeter, Christian; Bansmann, Michael; Dumitrescu, Roman; Anacker, Harald (Presentation and proceedings, Technology Transfer Society (T2S) Annual Conference, 2017)

Reifegradmodell für die Planung von Cyber-Physical Systems - Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman (Wissenschafts- und Industrieforum 2017 - Intelligente Technische Systeme, Band 369)

Schichtenmodell für die Entwicklung von Data Science Anwendungen im Maschinen- und Anlagenbau - Reinhart, Felix; Kühn, Arno; Dumitrescu, Roman (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys),)

Integrierte Entwicklung komplexer Systeme mit modellbasierter Systemspezifikation und -simulation - Eine Fallstudie zur Sensorauslegung in der Raumfahrt - Roßmann, Jürgen; Schluse, Michael; Rast, Malte; Hoppen, Martin; Atorf, Linus; Dumitrescu, Roman; Bremer, Christian; Hillebrand, Michael; Stern, Oliver; Schmitter, Peter (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Einsatz- und Nutzenpotentiale von Augmented Reality im Kontext von Industrie 4.0 - Röltgen, Daniel; Anacker, Harald; Dumitrescu, Roman (VDE Kongress 2016 Internet of Things, Mannheim, Deutschland, 7. - 8. Nov. 2016)

Einsatz von Leuchten zur Standortbestimmung in der Produktion - Falkowski, Tommy; Fechtelpeter, Christian; Peitz, Christoph; Kühn, Arno; Dumitrescu, Roman (VDE Kongress 2016, 7. - 8. Nov. 2016)

Reference Architecture and Maturity Levels for Cyber-Physical Systems - Westermann, Matthias; Anacker, Harald; Dumitrescu, Roman; Czaja, Anja Maria (2nd IEEE International Symposium on Systems Engineering 2016, Edinburgh, Scotland, 4. - 5. Okt. 2016)

Reliability in MID - barriers, potentials, fields of action - Fechtelpeter, Christian; Jürgenhake, Christoph; Dumitrescu, Roman; Mager, Thomas; Fritz, Karl-Peter; Grötzinger, Tobias; Müller, Hagen; Wild, Paul; Zimmermann, Andre (12th International Congress on Molded Interconnect Devices, Conference Proceedings , 28. - 30. Sep. 2016)

Classification of MID-prototypes - Jürgenhake, Christoph; Falkowski, Tommy; Dumitrescu, Roman (12th International Congress on Molded Interconnect Devices, Würzburg, 28. - 30. Sep. 2016)

Systematic for function-oriented development of spatial integrated circuit carriers - Jürgenhake, Christoph; Dumitrescu, Roman (International Design Conference - Design 2016, 16. - 19. Mai 2016)

Exhaustiveness of Systems Structures in Model-Based Systems Engineering for Mechatronic Systems - Kaiser, Lydia; Bremer, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

Function-based feasibility study and benchmark for MID concepts - Jürgenhake, Christoph; Falkowski, Tommy; Fechtelpeter, Christian; Dumitrescu, Roman (Sysint - 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)

A concept for managing information in early stages of product engineering by integrating MBSE and workflow management systems - Bretz, Lukas Helmut; Tschirner, Christian; Dumitrescu, Roman (IEEE ISSE: Proceedings of 2016 International Symposium on Systems Engineering)

Interdisciplinary System Architecture for Intelligent Technical Systems - Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman; Frank, Ursula; Hessenkämper, Axel (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition (IMECE2015))

Applying Model-Based Systems Engineering for Product Engineering Management - Concepts for Industrial Application - Tschirner, Christian; Bretz, Lukas Helmut; Dumitrescu, Roman; Gausemeier, Jürgen (1st International Symposium on Systems Engineering (IEEE ISSE), Rome, Italy, 28. - 30. Sep. 2015)

Potential of using model-based systems engineering to improve the development process of engineering-to-order products in the field of machinery and plant engineering - Rabe, Martin; Anacker, Harald; Westermann, Thorsten; Dumitrescu, Roman (4th International Conference on Advances in Mechanical Engineering, 16. - 27. Aug. 2015)

Architecture for Integrated Development of Complex Systems With Model-Based System Specification and Simulation - Roßmann, Jürgen; Schluse, Michael; Rast, Malte; Hoppen, Martin; Dumitrescu, Roman; Bremer, Christian; Hillebrand, Michael; Stern, Oliver; Blümel, Florian; Averdung, Christoph (ASME 2015 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Boston, USA, 2. - 5. Aug. 2015)

Improving order fulfillment processes with MBSE - Westermann, Thorsten; Anacker, Harald; Dumitrescu, Roman (20th International Conference on Engineering and Design (ICED15), Milan, Italy, 27. - 30. Jul. 2015)